2021
DOI: 10.1111/grow.12467
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge diffusion channels in Brazil: The effect of inventor mobility and inventive collaboration on regional invention

Abstract: The main goal of this paper is to evaluate the role of inventor mobility and inventive collaboration in Brazilian regional innovation. We take into account the regional knowledge production function (RKPF) to incorporate the regional interactions promoted by these two important knowledge diffusion channels. Using a dynamic panel with data from a unique combination of the Intellectual Property Database for Statistical Purposes (BADEPI v1.0) and the Annual Social Information Report of the Labor Ministry (RAIS), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…In this article, research and development (R&D) is interpreted as a process of generating new knowledge. Performance indicators for this process can be determined by tracking the research productivity of actors, which can be measured, for example, by the number of academic publications [4][5][6][7][8].…”
Section: Value Of the Datamentioning
confidence: 99%
“…In this article, research and development (R&D) is interpreted as a process of generating new knowledge. Performance indicators for this process can be determined by tracking the research productivity of actors, which can be measured, for example, by the number of academic publications [4][5][6][7][8].…”
Section: Value Of the Datamentioning
confidence: 99%
“…Nevertheless, this view has been increasingly challenged by many studies [9,10], which have indicated that knowledge can spread over long distances through mechanisms such as foreign direct investment [11,12], labor mobility [13,14], and technological proximity [15].…”
Section: Introductionmentioning
confidence: 99%